Violence at work in the series The Office from the perspective of epistemicide - Bizarria, Fabiana Pinto de Almeida; Pinheiro, Leonardo Victor de Sá; Barbosa, Flávia Lorenne Sampaio; Silva, Brunele Campos (Contextus - Revista Contemporânea de Economia e Gestão, 2025)
Contextualization: When analyzing workplace violence and subjectivation processes, epistemic violence is highlighted as a structural mechanism that delegitimizes and marginalizes the knowledge and perspectives of specific groups, consolidating dynamics of exclusion and social isolation. The TV series "The Office" presents an emblematic representation of this phenomenon through the disconnection between the main character's behavior, Michael, and employees' perceptions. This attitude manifests in practices that generate recurring feelings of disrespect and devaluation, highlighting the complex power and hierarchy relations that perpetuate symbolic violence in the workplace. Objective: To understand workplace violence and subjectivation processes from the epistemicide perspective, using the TV series "The Office" as a reference. Method: A qualitative, observational study was grounded in the "structured microanalysis". This method, anchored in thematic axes and subthemes, enabled the constructing of a network of meanings, allowing a systematic analysis of the investigated dynamics. Results: The study revealed the reproduction of inequalities and injustices in the workplace, with the characters demonstrating forms of resistance to these dynamics by seeking to assert their identities and validate their experiences against the dominance of hegemonic knowledge. This struggle for recognition and appreciation underscores the urgency of constructing inclusive work environments that respect and embrace diverse perspectives, promoting equity and justice in organizational relations. Conclusions: The findings emphasize the social and theoretical implications of epistemic violence in the workplace, highlighting how it devalues knowledge and perpetuates inequalities. The study contributes to understanding the dynamics of exclusion and resistance, offering a critical perspective on the impact of power relations on individual subjectivation. It also highlights the role of organizations in establishing practices that value the diversity of voices and knowledge.